2020
DOI: 10.1007/s40265-020-01445-2
|View full text |Cite|
|
Sign up to set email alerts
|

Treatment Sequencing for Anaplastic Lymphoma Kinase-Rearranged Non-Small-Cell Lung Cancer

Abstract: Non-small-cell lung cancer (NSCLC) accounts for about 85% of all lung cancer cases and is the leading cause of cancer-related deaths. Most NSCLC patients are diagnosed with advanced disease and require systemic treatment. Despite emerging advances in chemotherapy and immunotherapy, the prognosis of stage IV patients remains poor. However, the discovery of oncogenic driver mutations including mutations in the epidermal growth factor receptor (EGFR), the anaplastic lymphoma kinase (ALK) and others, characterize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 96 publications
(120 reference statements)
0
13
0
Order By: Relevance
“…To expand PFS and OS, it is crucial to think about evidencebased treatment sequencing. Every ALK TKI has its own advantages and disadvantages (122). Therefore, a second biopsy is recommended for gene sequencing when the patient is resistant (123).…”
Section: Discussionmentioning
confidence: 99%
“…To expand PFS and OS, it is crucial to think about evidencebased treatment sequencing. Every ALK TKI has its own advantages and disadvantages (122). Therefore, a second biopsy is recommended for gene sequencing when the patient is resistant (123).…”
Section: Discussionmentioning
confidence: 99%
“…However, because of the rareness of DCTN1‐ALK fusion in NSCLC patients, the efficacy and duration of ALK‐TKI treatment in this subset of patients remained poorly understood. Here, we identified a female patient in our center with concurrent DCTN1‐ALK (D27:A20) and ALK‐CLIP4 (A19:C12) fusions and reported that this patient achieved PR to first‐line crizotinib therapy with a progress‐free survival (PFS) of 12 months, which was very similar to that of patients carrying EML4‐ALK fusion 5 . This may be because of the fact, that like EML4 , the DCTN1 fragment also contains a functional region that can initiate ALK transcription and translation 4 …”
Section: Discussionmentioning
confidence: 74%
“…Here, we identified a female patient in our center with concurrent DCTN1-ALK (D27:A20) and ALK-CLIP4 (A19:C12) fusions and reported that this patient achieved PR to first-line crizotinib therapy with a progress-free survival (PFS) of 12 months, which was very similar to that of patients carrying EML4-ALK fusion. 5 This may be because of the fact, that like EML4, the DCTN1 fragment also contains a functional region that can initiate ALK transcription and translation. 4 It is worth noting that ALK-CLIP4 (A19:C12) rearrangement (Figure 3) was detected in both plasma and tumor tissue before crizotinib treatment.…”
Section: Discussionmentioning
confidence: 99%
“…ALK rearrangements (typical genomic architecture is provided in Figure 1, upper panel) are present in 2%–6% of NS‐NSCLC 10 . These genomic alterations are sensitive to different molecules, notably to next‐generation TKIs (such as alectinib, brigatinib, and lorlatinib), which if given upfront result in significantly longer survival compared to initial treatment with the first‐generation inhibitor crizotinib or chemotherapy 9,11–13 . Excluding presence of an ALK fusion is also crucial before starting immunotherapy, due to the lack of efficacy and increased toxicity of the immune checkpoints inhibitors (ICIs) in ALK‐ positive NSCLC patients 14–16 .…”
Section: Alk Ros1 Ntrk and Ret Fusions: The “Big Four” Fusion Targets...mentioning
confidence: 99%
“…Fusions were visualized using Arriba 9 chemotherapy. 9,[11][12][13] Excluding presence of an ALK fusion is also crucial before starting immunotherapy, due to the lack of efficacy and increased toxicity of the immune checkpoints inhibitors (ICIs) in ALKpositive NSCLC patients. [14][15][16] Besides a very low tumor mutational burden of ALK-positive tumors, uniquely below 3 mut/MB on average, 17 an immunosuppressive tumor microenvironment also appears to contribute to the inherent ICI resistance of these tumors.…”
Section: Alk Rearrangementsmentioning
confidence: 99%